2014
DOI: 10.1536/ihj.14-052
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of New Onset Atrial Fibrillation Through P Wave Analysis in 12 Lead ECG

Abstract: SummaryIt is unknown whether 12-lead ECG can predict new-onset AF. In the present study, we identified patients with new onset AF from our digitally stored ECG database, and the P wave morphologies were analyzed in their preceding sinus rhythm recordings as the precursor state for AF. The P wave was analyzed in the most recent ECG recording of sinus rhythm preceding new onset AF within 12 months. The duration and amplitude of P waves were analyzed in 12 leads and compared between the 2 groups with the other cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…15,[22][23][24][25] Increased interstitial fibrosis may explain inter-atrial conduction disturbances. 26) Mizuno, et al previously reported that inter-atrial conduction time determined using TTE and ECG was delayed in patients with progressive systemic sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…15,[22][23][24][25] Increased interstitial fibrosis may explain inter-atrial conduction disturbances. 26) Mizuno, et al previously reported that inter-atrial conduction time determined using TTE and ECG was delayed in patients with progressive systemic sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the consideration of single and same P wave vector in the ECG recording, some investigators have doubted the clinical usefulness of this dispersion, but our present and preceding studies and other investigators have stated that the P wave dispersion is a useful index with which to evaluate atrial electrophysiology. 6,11,12,[14][15][16]19) Because P wave dispersion is the relative parameter calculated from the other measurements, correction or adaptation of direct value by P wave duration or heart rate might be a possible method to obtain a parameter with absolute meaning, but because we could not find such a trial about correction in dispersion in the previous reports, we just used direct data of dispersion in this study. The mechanism underlying P wave dispersion change remains uncertain, but may partially be explained by the change in direction of the atrial activation vector.…”
Section: Parameters To Discriminate Between Paf and Persistent Afmentioning
confidence: 99%
“…This activation may be recorded in some leads, but is likely to not be detected in leads with a horizontal angle to the direction of vector. 6,16,26) This phenomenon may result in the pseudo-disappearance of the terminal portion of the P wave in some leads, resulting in the enlargement of P wave dispersion in all 12 leads. In the present study, P wave duration also tended to be longer in persistent AF patients than in PAF patients, but the difference was not significant.…”
Section: Parameters To Discriminate Between Paf and Persistent Afmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, it has been reported that P wave analysis in 12-lead electrocardiograms (ECG) can be useful for predicting new onset AF, 3) and genetic predisposition is the newest addition to the occurrence of structural or lone AF. Some AF specific genes found may contribute to the development of left atrium remodeling, 4) and several genetic loci have been identified for monogenetic AF, such as loci on chromosomes 1q21, 3p21, 11p15.5, 12p13, 21q22, 7q35-36, and 6q14- 16.…”
mentioning
confidence: 99%